FAKTOR YANG MEMPENGARUHI KELELAHAN MATA PADA TUKANG JAHIT DI KAMPUNG BARU KECAMATAN BAITURAHAMAN KOTA BANDA ACEH TAHUN 2021 - Hidayattullah (Jurusan Kesehatan Lingkungan, Poltekkes Kemenkes Aceh, 2022)
Introdaction one of the industrial sectors that are experiencing rapid development is the convection industry. Sewing work is currently done more using machines, in this case, sewing machines compared to hands, in 2016 WHO estimates that 153 million people in the world experience eye viruses or eye disorders. In 2016, 61% of Americans were very serious about work-related eye problems. workers admitted that they do work for 4 to 11 hours a day and the time for rest is not determined, the chairs used are not suitable, causing fatigue, ergonomics that do not match the tailor's body posture and the way he works, and stress that causes eye fatigue when the tailor has to work. focus on small objects when sewing. This type of research is quantitative research. Results, there is a relationship between age, length of work, chair, stress and ergonomics with eye fatigue with p-value 0.040, p-value 0.020, p-value 0.044, p-value 0.018, p-value 0.019. Based on these results, it can be concluded that there is a relationship between these factors and eye fatigue in tailors.